The Sphynx : the hairless cat - Quasha, Jennifer (New York : PowerKids Press, 2000)
Discusses the origin, history, and characteristics of the hairless cat known as Sphynx.
Includes index.
Keywords: Sphynx cat -- Juvenile literature; Sphynx cat; Cats